Peran Pengadilan Agama dalam Mewujudkan Efektivitas Konsep Sedekah Bernegara - Faruqi, Ahmad; Syahmedi, Ramadhan (Universitas Muara Bungo, 2024)
Alms is a means provided by Islam as a form of social assistance to the community. If we look at the word sadaqah, it is taken from the Arabic word which means